The aurora borealis as described in Norges Naturlige Historie (1752) / Natürliche Historie von Norwegen (1753) / Natural History of Norway (1755) - Aspaas, Per Pippin (Aurorae Borealis Studia Classica, 2019)
The seventh volume in the series consists of extracts from Erich Pontoppidan's Natural History of Norway, originally published in Danish in 1752 and soon followed by a German (1753) and an English edition (1755). All three editions are included, with extracts covering Pontoppidan's treatment of the aurora borealis and closely related subjects. They are introduced by a biographical essay and summaries of contents by Per Pippin Aspaas from UiT The Arctic University of Norway.